Deskripsi Motivasi Belajar Matematika Siswa di Kelas VIII SMPN 29 Padang - Yolanda, Septia Tri; Medika, Gema Hista; Rahmat, Tasnim; Firmanti, Pipi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The aim of this study is to describe the level of motivation to learn mathematics among Year 8 pupils at SMPN 29 Padang in the 2024/2025 academic year. This study employed a quantitative descriptive approach with a sample comprising all Year 8 students. Data collection was conducted through the distribution of a mathematics learning motivation questionnaire designed based on indicators of intrinsic and extrinsic motivation, supplemented by documentation as supporting data. The data obtained were analysed using descriptive analysis techniques, calculating the percentage for each motivation indicator to determine the category of students’ learning motivation levels. The results of the analysis indicate that students’ motivation to learn mathematics falls into the high category, with a percentage of 67.55%. The difference in percentages between the intrinsic and extrinsic motivation indicators was not particularly significant, indicating that the influence of internal and environmental factors on students’ learning motivation was relatively balanced. An increase in both types of motivation has the potential to drive mathematics learning motivation into a higher category, thereby having a positive impact on learning outcomes and students’ interest in mathematics learning.